Insights into SARS-CoV-2, the Coronavirus Underlying COVID-19: Recent Genomic Data and the Development of Reverse Genetics Systems. (24th October 2020) - Silva, Severino Jefferson Ribeiro da; Germano Mendes, Renata Pessôa; Alves da Silva, Caroline Targino; Lorusso, Alessio; Kohl, Alain; Pena, Lindomar
Abstract : The emergence and rapid worldwide spread of a novel pandemic of acute respiratory disease – eventually named coronavirus disease 2019 (COVID-19) by the World Health Organization (WHO) – across the human population has raised great concerns. It prompted a mobilization around the globe to study the underlying pathogen, a close relative of severe acute respiratory syndrome coronavirus (SARS-CoV) called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Numerous genome sequences of SARS-CoV-2 are now available and in-depth analyses are advancing. These will allow detailed characterization of sequence and protein functions, including comparative studies. Care should be taken when inferring function from sequence information alone, and reverse genetics systems can be used to unequivocally identify key features. For example, the molecular markers of virulence, host range and transmissibility of SARS-CoV-2 can be compared to those of related viruses in order to shed light on the biology of this emerging pathogen. Here, we summarize some recent insights from genomic studies and strategies for reverse genetics systems to generate recombinant viruses, which will be useful to investigate viral genome properties and evolution.